2018
DOI: 10.2174/1381612824666180723161811
|View full text |Cite
|
Sign up to set email alerts
|

Where is the Clinical Breakthrough of Heme Oxygenase-1 / Carbon Monoxide Therapeutics?

Abstract: Heme oxygenase (HO), the rate-limiting step in the degradation of heme to biliverdin, ferrous ion, and carbon monoxide (CO), is an ancestral protective enzyme conserved across phylogenetic domains. While HO was first described in the late 1960s and progressively characterized in the following decades, there has been a surge of innovation over the past twenty years in efforts to leverage the cytoprotective power of HO in a clinical setting. Despite the plethora of preclinical data indicating extraordinary thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…We first performed immunostaining to confirm the location of HO-1 in RAW 264.7 macrophages, as shown in Supplementary Figure S2A . Previous studies have shown that HO-1 localizes to several compartments within the cell, including the mitochondria [ 22 ]. Double staining with the mitochondria-specific marker MitoTracker indicated that HO-1 localized to the cytoplasm of macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…We first performed immunostaining to confirm the location of HO-1 in RAW 264.7 macrophages, as shown in Supplementary Figure S2A . Previous studies have shown that HO-1 localizes to several compartments within the cell, including the mitochondria [ 22 ]. Double staining with the mitochondria-specific marker MitoTracker indicated that HO-1 localized to the cytoplasm of macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…HO-1, a 32 kDa enzyme containing 288 amino acid residues, is a stress-induced isoform present throughout the body. HO-1 has been reported in the mitochondria, cell nucleus, and plasma membrane [21]. HO-1 can attenuate oxidative damage and protect the myocardial, neurological and renal I/R injury in previous research and the expression of HO-1 in response to different inflammatory mediators may contribute to the resolution of inflammation and has protective effects against oxidative injury [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of HO-1 or exposure to CO offer dose-dependent anti-inflammatory and cytoprotective effects ( Otterbein et al, 2016 ). The cytoprotective effects of CO were first demonstrated in acute lung injury, and these findings rapidly expanded through the work of numerous laboratories to most models of acute organ injury ( Hopper et al, 2018 ). Administration of exogenous CO or higher HO-1 activity increases the expression of anti-inflammatory cytokines and reduces expression of multiple pro-inflammatory cytokines during acute pulmonary inflammation ( Konrad et al, 2016 ; Zhang et al, 2019 ).…”
Section: Clinical Insightsmentioning
confidence: 99%